Penerapan Strategi Manajemen Mutu Untuk Meningkatkan Validitas Keputusan Berbasis Fakta Di Sekolah Menengah Pertama - Sitorus, Ellen Rotua Basaria; Widiayati, Widiayati; Azainil, Azainil (Pendas Mahakam : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2024)
This study aims to evaluate the implementation of quality management strategies at SMP Negeri 5 Kelay, East Kalimantan, with a focus on improving the validity of data-based decisions to improve the quality of education. The research methods used include qualitative and quantitative approaches by conducting interviews, observations, and document analysis. The results of the analysis show that schools face challenges related to inadequate technological infrastructure, teaching staff skills in data management that need to be improved, and coordination between stakeholders that is not optimal. Even so, there have been efforts to increase the capacity of human resources and information technology infrastructure in the school. The recommendations from this study include the need to develop a more structured and integrated data management system, increase training for teaching staff in effective data management, and improve coordination between stakeholders to ensure more accurate and efficient data-driven decision-making. This effort is expected to contribute significantly to improving the quality of education at SMP Negeri 5 Kelay, East Kalimantan. Keywords: Strategy, Quality Management, Validity, Fact-Based Decisions, Junior High School